Pancreatic Beta-cell function and degree of Insulin resistance among newly detected type 2 diabetics and their correlation with anthropometric, glucose, and lipid parameters: An Observational cross-sectional study - Saha, Avijit (Asian Journal of Medical Sciences, 2022)
Background: Insulin resistance is a major cause for developing type 2 diabetes. However, simultaneously pancreatic beta-cell dysfunction must coexist in for clinical occurrence of type 2 diabetes (T2D). Hence, knowledge regarding residual beta-cell function and degree of insulin resistance is required while treating type 2 diabetic patients. Aims and Objectives: The present study was done to estimate degree of insulin resistance (homeostatic model assessment insulin resistance - HOMA-IR) and pancreatic beta-cell functional capacity (HOMA-B%) among newly detected type 2 diabetics and correlation of these with anthropometric, glucose, and lipid parameters. Materials and Methods: This was an observational cross-sectional study conducted in 100 newly diagnosed type 2 diabetic patients. Detailed anthropometric and clinical examination were carried out. Venous blood samples were drawn for fasting plasma glucose, c-peptide, fasting insulin level, hemoglobin A1C (HbA1C), lipid profile, and postprandial glucose. HOMA-IR and HOMA-B% were calculated using HOMA 2 calculator and correlations were calculated between the study variables. Results: The mean age of the study population was 45.55±11.64 years and 58% of study participants were male. The mean HOMA-IR and HOMA-B% were 2.55±1.75 and 40.67±23.55%, respectively. HOMA-IR positively correlated with abdominal circumference, triglyceride to HDLc ratio, and negatively correlated with HDLc. There were statistically significant negative correlations between HOMA-B% and fasting glucose(r=−0.48, P<0.001), 2 hr post prandial glucose (r=−0.37, P<0.001 and HbA1C (r=−0.24, P=0.01). Conclusion: This study found more reduced beta-cell function compared to reduced insulin sensitivity in new T2D mellitus patients. Hence, this kind of functional assessment needs to be done while selecting appropriate anti-diabetic drugs for a particular patient.